AB0079 Alfacalcidol suplementation modulates cytokine production in peripheral blood mononuclear cells culture of patients with active rheumatoid arthritis. (12th June 2018) - Zivanovic Radnic, T.; Simic Pasalic, K.; Sefik Bukilica, M.; Damjanov, N.; Vojinovic, J.
Abstract : Background: Hormone D and its analogues display immunomodulatory activities that provide a beneficial effect in immunoinflammatory diseases. However, whether this hormone has an additive immunosuppressive effect when it is used with corticosteroids has not been investigated, although these agents are commonly used together. Objectives: Testing the immunomodulatory in vitro effects of vitamin D analogue, alfacalcidol, in peripheral blood mononuclear cells (PBMC) cultures of patients with active rheumatoid arthritis (RA). Methods: Sixteen patients with active RA were enrolled in the study. Patients PBMCs were isolated, stimulated with PMA/Ionomycin and cultivated for 48 hours at 37°C, 5% CO2 in cell cultures medium with or without supplementation. In vitro effects of supplementation with alfacalcidol (concentration 10 nM), calcitriol (concentration 10 nM), methylprednisolone (concentration 400 nM) and cotreatment with alfacalcidol/methylprednisolone on cytokine production were studied. Stimulated production of cytokines IL-6, IL-17, IL-21, TNF-α, IL-4, IL-10, TGF-β and IFN-γ were determined in cell culture supernatant by standard ELISA method. Results: In vitro alfacalcidol supplementation reduces the production of proinflammatory cytokines IL-17 (p=0.001), IL-21 (p=0.001), TNF-α (p=0.002) and IL-6 (p=0.4), and induce more intense anti-inflammatory cytokine production IL-4 (p<0.0001), IFN-γ (p=0.05), TGF-β (p<0.0001) and IL-10 (p=0.09), in PBMC cultures of patients with active RA. There was no significant difference between the effects of alfacalcidol and calcitriol, except decreased TGF-β production (p=0.535) after calcitriol supplementation. Methylprednisolone supplementation leads to a significant reduction of the IL-6 (p=0.002), IL-17 (p=0.0001), TNF-α (p=0.0001) and IL-4 (p=0.017) production, while increased production of IL-21, IL-10, IFN-γ didn't reach statistical significance. Cotreatment with alfacalcidol and methylprednisolone leads to additional, more significant reduction of IL-17 (p=0.0001) and TNF-α (p<0.0001) in PBMCs of patients with active disease. Conclusions: Alfacalcidol, in vitro, showed a significant immunomodulatory effect through the specific inhibition of Th1- cytokine production, while Th2 cell response was enhanced – "Th2 switch". Our results demonstrate that alfacalcidol has significant additive effects on glycocorticoid-mediated inhibition of Th1 cytokine production when combined with methylprednisolone. These findings demonstrate the potential use of alfacalcidol as an immunosuppressive agent when combined with corticosteroids in Th1, but not Th2, immune response. References: [1] Živanović Radnić T, Simić-Pašalić K, Šefik Bukilica M, Misirlić Denčić S, Isaković AM, Stojković T, Petronijević N, Damjanov N, Vojinović J. J. Serb. Chem. Soc2016. doi:10.2298/JSC160506039Z [2] Cutolo M. Vitamin D and autoimmune rheumatic diseases. Rheumatology2008. [3] Andjelkovic Z, Vojinovic J, Pejnovic N, Popovic M, Dujic A, Mitrovic D, et al. Disease modifynig and immunoregulatory effects of high oral dose 1a(OH)D3 in rheumatoid arthritis patients. Clin Exp Rheumatol1999;17(4):59–62. Disclosure of Interest: None declared